Study of Package Fraction Fraction Sensitivity TRISO in Design of HTR Pebble Bed Criticality - Zuhair Zuhair; Suwoto Suwoto (Natural B, Journal of Health and Environmental Sciences, 2012)
HTR is a high temperature reactor used for electricity production and process heat applications such as hydrogen production, desalination of sea water, enhanced oil recovery and so on. HTR is designed based on the utilization of TRISO fuel particles that can prevent strongly the escape of fission products even at temperatures above 1600 oC. TRISO particles packing fraction is one of four key parameters that are essential in HTR design besides radius of the kernel, kernel density and fuel enrichment. This paper discusses the sensitivity of TRISO particles packing fraction that impacts to the loading of uranium in the fuel pebble, the long cycle of reactor operation and achievable maximum fuel burn-up. With the capability of Monte Carlo transport code MCNP5, all components of the reactor, starting from TRISO particles, were modeled in detail and explicit and calculated using the continuous energy nuclear data library ENDF/B-VI. The results show that the value of effective multiplication factor (keff) has a tendency to increase with decreasing particle TRISO packing fraction and to decrease with increasing fuel burn-up. Keff values decrease with increasing TRISO particle packing fraction both at the beginning of cycle (BOC) and at the end of cycle (EOC). Reactivity swing is also very sensitive on the TRISO particles packing fraction. From the analysis, it can be concluded that TRISO particles packing fraction greatly affects the neutronics performance of HTR pebble bed design. Packing fraction can change the effective multiplication factor (keff) and the swing reactivity with similar behavior.